Theory of planned behavior and smoking: meta-analysis and SEM model - Gabriela Topa; Juan Antonio Moriano (Dove Medical Press, 2010)
Gabriela Topa, Juan Antonio MorianoDepartment of Social and Organizational Psychology, UNED, Madrid, SpainAbstract: To examine if the theory of planned behavior (TPB) predicts smoking behavior, 35 data sets (N = 267,977) have been synthesized, containing 219 effect sizes between the model variables, using a meta-analytic structural equation modeling approach (MASEM). Consistent with the TPB's predictions, 1) smoking behavior was related to smoking intentions (weighted mean r = 0.30), 2) intentions were based on attitudes (weighted mean r = 0.16), and subjective norms (weighted mean r = 0.20). Consistent with TPB's hypotheses, perceived behavioral control was related to smoking intentions (weighted mean r = -0.24) and behaviors (weighted mean r = -0.20) and it contributes significantly to cigarette consumption. The strength of the associations, however, was influenced by the characteristics of the studies and participants.Keywords: theory of planned behavior, smoking, meta-analysis, structural equation modeling